Functional state of the brain bioelectric activity in treatment of diaphyseal lesions of the radius using the transosseous osteosynthesis of the wire and rod arrangement - I. N. Kinash; M. E. Puseva; Ch. Z. Butaev; T. K. Verkhozina; E. G. Ippolitova (Acta Biomedica Scientifica, 2021)
Radial fracture is the most common trauma to the musculoskeletal system and accounts for 50 % of traumatic injuries to the bones of the upper limb. Disability in patients with fractures of the forearm bones ranges from 6 to 8 months, so the choice of the most effective method of treatment is very relevant. Currently, an important point is the tendency of optimizing the transosseous method by eliminating the disadvantages and looking for new advantages of external fixation. Bone fracture and associated surgical intervention are always accompanied by varying degrees of changes in the links of the central nervous system, hemodynamics and metabolism. In order to study the bioelectrical activity of the brain in 47 patients with a fracture of the radial diaphysis treated in the Traumatology Department of the Irkutsk Scientific Centre of Surgery and Traumatology, in the pre- and postoperative period we compared EEG indicators of two variants of the layout of the external fixation apparatus (EF): wire and rod. Analysis of the rhythms of bioelectrical activity of the brain in both groups in the preoperative period revealed a normal zonal distribution with the dominance of the alpha rhythm on the EEG, which generally reflects a rather high degree of organization of neuroactivity and indicates the stability of cerebral homeostasis. At the same time, in the group of patients with a wire-mounted EF device in the postoperative period, EEG indices significantly differed from the values of the norm and ndicators in the group with a rod-shaped arrangement. A decrease in the amplitude of alpha and beta rhythms was noted, as well as a shift in the frequency of bioelectric activity towards slow waves, which is a sign characteristic of discirculatory encephalopathy. An EEG study using the method of transosseous osteosynthesis with EF devise of a rod assembly showed its greater efficiency compared to the use of an EF device of a wire assembly during treatment and rehabilitation. Thus, the study of the bioelectric activity of the brain is a reliable method for assessing its functional state after an injury, as well as the effectiveness of the treatment.